Motif Batik Tradisional Surakarta Tinjauan Makna Filosofis dan Nilai-nilai Islam - Siti Nurlaili Muhadiyatiningsih; Ari Hikmawati (Al-Ulum, 2018)
This article discussed the various of traditional Batik motives in Surakarta based on the overview of philosophy meaning and Islamic values. Through the symbolic descriptive interpretation approach, the author tried to find out the meaning of motive in Batik Surakarta. The result of the research shown that at least ten kinds of traditional batik motives in Surakarta. Each of the motives reflected the philosophy meaning and Islamic values. Philosophically, it was found that the meaning in Batik motive is influenced by Hindu teaching, Sangkan Paraning Dumadi. Meanwhile, in Islamic values point of view, traditional motive batik in Surakarta are reflecting the life chronology of human being, from they are in pregnancy phase to the death phase. The Islamic teaching are presented in batik motive covers the theological concept, law concept, and social concept.